2020
DOI: 10.1093/ofid/ofaa279
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Discordant Rifampicin Susceptibility Test Results Obtained Using GeneXpert vs Phenotypic Drug Susceptibility Testing

Abstract: Abstract Background The three-month difference in turnaround time between Xpert and conventional phenotypic drug susceptibility testing (pDST) causes patient treatment challenges when pDST rifampin (RIF) susceptibility results and earlier Xpert results disagree, resulting in unnecessary tuberculosis (TB) patient exposure to toxic second-line drugs. Here, the prevalence of discordant RIF susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…A recent study by Huo and colleagues found that cases with very low bacterial load were more likely to be misdiagnosed with Xpert resistance to RIF. Notably, in the present study, four quantifications of resistant samples that were "very low" or "low" were positive for Xpert and negative for culture, which justifies further investigations [45].…”
Section: Plos Onesupporting
confidence: 54%
See 1 more Smart Citation
“…A recent study by Huo and colleagues found that cases with very low bacterial load were more likely to be misdiagnosed with Xpert resistance to RIF. Notably, in the present study, four quantifications of resistant samples that were "very low" or "low" were positive for Xpert and negative for culture, which justifies further investigations [45].…”
Section: Plos Onesupporting
confidence: 54%
“…Of the patients included in this study, 35.8% (266/743) were HIV-positive and most of them already met the criteria for AIDS diagnosis. Low T-CD4 lymphocyte count is associated with advanced stage of TB/HIV coinfection along with immunological impairment and critical clinical conditions [ 42 45 ]. Comparing the results of the Xpert in HIV-positive and -negative populations, no significant differences were observed in the test performance.…”
Section: Discussionmentioning
confidence: 99%
“…Colonies were harvested and then subjected to phenotypic DST using a commercial microdilution method. 15 Growth of MTB at a concentration of RIF of 1.0 mg/L was considered to be a positive test result for RIF resistance. All isolates were stored at −80°C in Middlebrook 7H9 medium supplemented with 10% OADC and 5% glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…For example, synonymous RRDR mutations and the aforementioned rpoB T427A, should it be truly neutral, cause systematic false resistance results (35,39). In addition, Xpert has a higher false resistance rate with very low bacillary load samples (37,(40)(41)(42). The latter limitation does not apply to Xpert MTB/RIF Ultra, which also was designed to avoid false resistance results due to synonymous mutations at codons 432 and 433 of rpoB, although this assay misses some resistance mutations in this region of rpoB instead and other synonymous mutations still cause false resistance (37,39).…”
Section: Genotypic Ast For Rifmentioning
confidence: 99%